1996
DOI: 10.1159/000196546
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Epithelial Cells Release Cyclooxygenase-Dependent and Cyclooxygenase-lndependent Factors That Inhibit Cholinergic Contraction of Canine Airway Smooth Muscles

Abstract: We observed the effects of supernatants from cultured epithelial cellson the contraction of tracheal smooth muscle evoked by acetylcholine (ACh) or by electrical field stimulation (EFS). Cultured canine tracheal epithelial cells were incubated in Krebs solution with or without indomethacin (10-5 M) for 30 and 120 min. The amplitude of the tracheal smooth muscle contractions evoked by EFS or exogenously applied ACh were measured before and after the application of each supernatant in the combined pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In our study, however, the administration of indomethacin or L-NNA did not significantly alter the basal tone in rat tracheal rings, which indicated that the basal production of prostanoids and NO was low in rat airways as described previously (35). Our study also demonstrated that either pretreatment with indomethacin A B or exogenously applied PGE 2 significantly attenuated the inhibitory effect of ACh on EFS-evoked contraction of rat tracheas, which is consistent with previous reports in canine airways (36). These observations suggested that ACh might trigger the release of PGE 2 , which acted on tracheal smooth muscle and induced relaxation.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, however, the administration of indomethacin or L-NNA did not significantly alter the basal tone in rat tracheal rings, which indicated that the basal production of prostanoids and NO was low in rat airways as described previously (35). Our study also demonstrated that either pretreatment with indomethacin A B or exogenously applied PGE 2 significantly attenuated the inhibitory effect of ACh on EFS-evoked contraction of rat tracheas, which is consistent with previous reports in canine airways (36). These observations suggested that ACh might trigger the release of PGE 2 , which acted on tracheal smooth muscle and induced relaxation.…”
Section: Discussionsupporting
confidence: 93%
“…The prostaglandins PGE 2 , PGI 2 and small amounts of PGF 2α and TxA 2 are all produced in airway epithelium following activation of cyclooxygenase enzymes, with PGE 2 being produced in the greatest amounts. PGE 2 is generally described as a bronchoprotective mediator due to its inhibitory effects on airway smooth muscle, mucus secretion and nerve activity 72–75 . However, PGE 2 may also promote a Th‐2 bias for intraepithelial dendritic cells, suggesting that it has complex effects within the airways 76…”
Section: Epithelial Functionmentioning
confidence: 99%
“…PGE 2 is generally described as a bronchoprotective mediator due to its inhibitory effects on airway smooth muscle, mucus secretion and nerve activity. [72][73][74][75] However, PGE 2 may also promote a Th-2 bias for intraepithelial dendritic cells, suggesting that it has complex effects within the airways. 76 Originally, it was thought that bone-marrow derived cells were the main cells expressing lipoxygenase enzymes.…”
Section: Arachidonic Acid Metabolitesmentioning
confidence: 99%